Efficacy, Safety, and Tolerability of Theta-Burst Stimulation in Mixed Depression: Design, Rationale, and Objectives of a Randomized, Double-Blinded, Sham-Controlled Trial - Tavares, Diego Freitas; dos Santos, Carla Garcia Rodrigues; Valiengo, Leandro Da Costa Lane; Klein, Izio; Borrione, Lucas; Forte, Pamela Marques; Brunoni, Andre R.; Moreno, Ricardo Alberto (Frontiers in Psychiatry, 2020)
INTRODUCTION: Mixed-specifier mood disorders are probably a different subgroup in terms of response to treatment, socio-demographic parameters, course and family history. Here we describe the rationale and design of a clinical trial aimed to test the efficacy, safety and tolerability of a non-pharmacological treatment known as theta-burst stimulation (TBS) for treating the mixed depressive episodes of both bipolar (I or II), and unipolar depression. METHODS: The study is designed as a randomized, sham-controlled, double-blinded clinical trial evaluating TBS for the treatment of moderate or severe major depressive episodes with mixed features of patients receinvig at least one first or second line pharmacological treatment for depressive episodes without adequate response. Ninety adult (18 to 65 yo) patients will be enrolled and submitted to 6-week (comprising 5 consecutive days a week sessions for the first 3 weeks and then 2 days a week for a further 3 week) of inhibitory followed by excitatory TBS in dorsolateral prefrontal cortex. Participants will be assessed using clinical and neuropsychological tests before and after the intervention. The primary outcome is change in Montgomery-Asberg Depression Scale (MADRS) score over time and across groups. Cognitive parameters will also be assessed with neuropsychological tests. RESULTS: The clinical results will provide evidence about TBS as an adjunctive treatment for mixed depression treatment and neuropsychological parameters will contribute towards an improved understanding the effects of TBS in cognition. CONCLUSION: Our results could introduce a novel therapeutic technique for mixed depressive episodes of both bipolar and unipolar disorders. Clinical trial registration: www.clinicaltrials.gov; NCT04123301; date of registration: 10/10/2019; URL: https://clinicaltrials.gov/ct2/show/NCT04123301?term=NCT04123301&rank=1